The influence of sports-related concussion on cognition and landing biomechanics in collegiate athletes - Avedesian, J. M.; Covassin, T.; Baez, S.; Nash, J.; Dufek, J. S. (Scandinavian Journal of Medicine & Science in Sports, 2024)
Injury surveillance data indicate that collegiate athletes are at greater risk for lower extremity (LE) injuries following sports-related concussion (SRC). While the association between SRC and LE injury appears to be clinically relevant up to 1-year post-SRC, little evidence has been provided to determine possible mechanistic rationales. Thus, we aimed to compare collegiate athletes with a history of SRC to matched controls on biomechanical and cognitive performance measures associated with LE injury risk. Athletes with a history of SRC (n = 20) and matched controls (n = 20) performed unanticipated bilateral land-and-cut tasks and cognitive assessments. Group-based analyses (ANOVA) and predictive modeling (C5.0 decision tree algorithm) were used to compare group differences on biomechanical and cognitive measures. Collegiate athletes with a history of SRC demonstrated approximately six degrees less peak knee flexion on both dominant (p = 0.03, d = 0.71) and nondominant (p = 0.02, d = 0.78) limbs during the land-and-cut tasks compared to controls. Verbal Memory, knee flexion, and Go/No Go total score (C5.0 decision tree algorithm) were identified as the strongest indicators of previous SRC injury history. Reduced knee flexion during sport-specific land-and-cut tasks may be a mechanism for increased LE injury risk in athletes with a history of SRC. There appears to be multiple biomechanical and cognitive predictors for identifying previous SRC in collegiate athletes, providing evidence to support a multifactorial SRC management strategy to reduce future injury risk.